Las medidas Covid-19 para la reapertura de restaurantes de servicio completo: el impacto en la intención de recomendación de boca en boca - Reich López, Christian; Teran Cazares, María Mayela; López Pérez, Jesus Fabián (Innovaciones de Negocios, 2021)
In late December 2019, authorities in China spotted a large number of pneumonia cases of unknown cause, linked to a seafood market in Wuhan, Hubei Province, China (Zhu et al., 2020). These cases were the consequence of a novel virus, later named Covid-19, which spread all around the world, and was finally declared as a pandemic by the World Health Organization on January 30, 2020. This changed the way the world works in several industries, including hospitality.